Acne and dairy products in adolescence: results from a Norwegian longitudinal study. (16th July 2016) - Ulvestad, M.; Bjertness, E.; Dalgard, F.; Halvorsen, J.A.
Abstract: Background: Acne is a very common skin condition, and it is of great interest to elucidate lifestyle factors that may contribute to its occurrence. In the last decade, the acne‐diet connection has been brought back to credibility. Objective: To examine whether high intakes of dairy products in early adolescence is associated with moderate to severe acne in later adolescence. Methods: The study is a longitudinal, questionnaire‐based population study of Norwegian adolescents. Students attending the 10th grade (15–16 years old) of compulsory schooling in Oslo in 2000–2001 and the 13th grade (18–19 years old) 3 years later, in 2004, were invited. Dairy product consumption was self‐reported at age 15–16 and acne severity was self‐assessed and reported at age 18–19. Results: The overall prevalence of moderate to severe acne was 13.9%. High intakes (≥2 glasses per day) of full‐fat dairy products were associated with moderate to severe acne. In boys with exclusively high intakes of full‐fat dairy products, the odds ratio for acne was 4.81 (1.59–14.56). A high total intake of dairy products was associated with acne in girls (OR 1.80, 1.02–3.16). No significant associations were found between acne and intake of semi‐skimmed or skimmed dairy products, and not with moderate intakes of any fat variety of dairy products. Conclusion: This study shows association between high intakes of dairy products and acne in adolescence. Our findings support a hypothesis suggesting that dairy consumption may be a factor contributing to acne. The study is based on multiple hypothesis testing, and the methodological limitations must be considered when interpreting the results.